Electrokinetic remediation approach towards heavy metals extraction from Bukit Ibam iron mine tailing at Pahang, Malaysia - Wahab, A.; Muzamir, Hasan (The European Association of Geoscientists and Engineers (EAGE), 2024)
This study focuses on extracting heavy metals from active and abandoned mining tailings, and reservoirs for lead, copper, zinc, arsenic, manganese, iron, chromium, cadmium, and nickel—critical environmental contaminants with substantial risks to human health and ecosystems. Rapid industrialization and intensive agriculture have heightened concerns about these elements, necessitating monitoring of their long-term impacts on human health, soil quality, water resources, and river ecosystems. Prudent management of the mining sector is crucial to mitigate its adverse environmental effects, such as climate change, soil, air, and water pollution, significantly affecting food security and aquatic life due to heavy metal contamination—especially arsenic, lead, copper, and nickel, causing extensive harm. Addressing these issues requires robust environmental management and eco-friendly technologies like electrokinetic remediation (EKR). Soil samples from Bukit Ibam, Pahang, Malaysia, revealed elevated concentrations of As (105.5 mg/kg), Pb (618.9 mg/kg), Cu (319.8 mg/kg), and Ni (194.8 mg/kg) exceeding permissible limits. EKR application at 100 V and 150 V for 4 and 8 hours respectively exhibited substantial removal efficiencies: 71% for As, 62.3% for Pb, 67.1% for Cu, and 47.9% for Cr. Augmenting EKR energy and duration demonstrates its promising, eco-friendly potential without compromising environmental safety.